Similarities and differences - Stainton-Rogers, Wendy; Sealey, Frances (Milton Keyes : Open University Educational Enterprises, 1982)
This programme examines whether behaviour is different when interaction takes place between different type of personality. Its also considers whether situational factors makes any significant difference to the outcome.
Keywords: Personality and situation